Análisis de la arquitectura empresarial de una empresa vinculada al sector energético y diagnóstico de su estado actual (2020)
The objective of this project consists of the analysis of the business architecture in its current state of a company with a good position in its respective market with a growth projection that can be improved both in the short and medium-term. It seeks to make a diagnosis from different points of view, going through the business, financial, strategic models, evaluating operating models, and reaching one of the most significant axes: technology and its analysis from information, applications, and the infrastructure.